Ανίχνευση του mycobacterium avium subsp paratuberculosis σε νωπό αγελαδινό γάλα και βρεφικές τροφές σε σκόνη με τη μέθοδο των βακτηριοφάγων - Χατζητοφή, Μαρία (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, 2012)
Mycobacterium avium subspecies paratuberculosis (ΜΑΡ) is the causative agent of Johne’s disease in cattle and other ruminants and may have a role in the development of Crohn΄s disease in humans. Detection of MAP with culture is time consuming because the incubation lasts at least four months, due to the very slow growth rate of the microorganism. New methods based on bacteriophages are promissing to be more sensitive and rapid. In this study, samples of Bulk Tank Milk (BTM) from 10 different cattle farms and 32 samples of infant powder milk were examined for MAP with a combined phage-PCR assay. Sampling was performed in two different periods and during the first period of sampling, five cattle farms (50%) were infected with MAP and nine cattle farms (90%) were infected with mycobacteria. Over the second sampling period, four farms (40%) were MAP positive whereas the prevalence rate of mycobacteria remained steady. Out of a total 32 infant powder milk samples examined with the bacteriophage method, only one was positive. This study proves that the bacteriophage method can be used for the detection of MAP, not only in samples of BTM but also in samples of infant powdered milk formulas. New rapid detection methods are needed for MAP in order to apply better control measures aiming at eradicating it from the milk and milk products supply chain.
Keywords: Bacteriophages; Farming; Bακτηριοφάγος; Kτηνοτροφία